Effect of salt reduction on growth of Listeria monocytogenes in broth and meat and poultry systems - Harper, Nigel Murray (Kansas State University, 2011)
Salt is used as a preservative in food. Reducing sodium in food, due to its link to hypertension, and replacing NaCl with other types of salt could have an effect on food safety. The main objective was to determine differences in salts and salt substitutes on growth of Listeria monocytogenes in broth and meat and poultry systems. Salts (NaCl, KCl, CaCl2, MgCl2, sea salt, and replacement salt) were added (0.5, 1, and 2.5%) to Listeria monocytogenes (five-strain cocktail) inoculated Listeria enrichment broth at 25 °C and sampled at 0, 24, and 48 h. Results showed that MgCl2, regardless of concentration, caused Listeria monocytogenes populations to grow approximately 0.6 log CFU/mL more (P < 0.05) than the other salts. Fresh ground beef, pork, and turkey with NaCl, KCl, CaCl2, MgCl2, sea salt, and replacement salt (2.0%) were inoculated with Listeria monocytogenes (five-strain cocktail) to determine growth/survival during 5 d at 4 °C to simulate a pre-blend process. Listeria monocytogenes populations significantly decreased (0.41 log CFU/g) during the storage time in beef, however no differences (P > 0.05) were observed over time in pork or turkey. Salt type did not affect (P > 0.05) Listeria monocytogenes populations during pre-blend storage. However, salts (MgCl2 and NaCl) allowed growth (P < 0.05) of aerobic populations during storage. Emulsified beef and pork products were processed with NaCl, KCl, sea salt and a NaCl/KCl blend (2%) and post-processed surface inoculated with Listeria monocytogenes (five-strain cocktail) to determine growth/survival at 4 °C for 28 d. Pork products showed greater (P < 0.05) Listeria monocytogenes population growth at all sampling times (0, 7, 14, 21, and 28 d) than beef products; whereas salt type had no effect on Listeria monocytogenes populations with sampling times pooled for data analysis. Although salt types were not shown to have an impact on Listeria monocytogenes growth/survival in pre-blend and emulsified post-processed surface inoculated meat products, pork and turkey pre-blends and emulsified pork had greater Listeria monocytogenes populations compared to beef products. These studies demonstrate that sodium reduction or replacement may not affect safety of pre-blends and emulsified meat and poultry products.
Keywords: Listeria monocytogenes; Salt; Beef; Pork; Turkey; Sodium; Food Science (0359)